Analisis Karakteristik Petani Dan Pendapatan Usahatani Duku (Lansium Domesticum Corr.) Di Kabupaten Kudus - Muhamad Imanuddin (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Kudus Regency has a distinctive variety of duku plant known as duku Sumber. The characteristics of duku farmers in Kudus Regency are different. The aim of this research is to describe the characteristics of duku farmers in Kudus Regency and determine the income of duku farming in Kudus Regency. The basic method used in this research is the descriptive method. The research location was determined purposively in the duku producing area in Kudus Regency. The research sample was 65 respondents. Table analysis was carried out to describe the characteristics of duku farmers, cost and income analysis was carried out to determine the costs and income incurred by farmers in duku farming. The results of the research show that the majority of duku farmers in Kudus Regency are of productive age and use duku Sumber farming as a side job. The highest level of education is high school graduates with an average of 25.95 years of duku farming experience. On average, farmers have 3.35 duku plants. The average duku production is 113 kg/plant with an average selling price of Rp. 28,359 per kilogram. Receipt Rp. 4,839,615,- per plant obtained from an average cost of Rp. 2,195,919,- in the form of fixed costs of Rp. 1,826,557.58,- and variable costs of Rp. 369,362,-. The income generated is IDR. 13,015,267.61 per plant.